Variability of anthropogenic and natural compounds in high altitude-high accumulation alpine glaciers - MAGGI, VALTER; VILLA, SARA; FINIZIO, ANTONIO; DELMONTE, BARBARA; Casati, P; Marino, F. (Hydrobiologia, 2006)
Mid-latitude glaciers represent one of the most important archive of environmental and atmospheric data. In the absence of summer melting, the accumulation of snow on the upper part of mountain chains can allow preservation of the chemical, isotopic and insoluble mineral dust composition of the atmosphere in stratigraphic sequence. The European Alps are located in an area of intense human impact, lying in between some of the most industrialized countries of the world (Italy, France, Germany) and facing the Mediterranean basin. Ice cores recovered from alpine sites above 4000 m a.s.l., where the mean annual temperature is normally below -10 degrees C, allow obtaining precious environmental records. While low-accumulation high-altitude sites provide the longest alpine sequences (Colle Gnifetti, Italian Alps), high-accumulation sites as Col du Dome (CDD, French Alps) and Colle del Lys (CDL, Italian Alps), both located about 4250 m a.s.l. are suitable for obtaining information about the seasonal variability of some compounds. We synthesize in this work the main results from alpine ice cores investigations held by various authors, focusing on high-altitude-high-accumulation sites in particular. Behind the seasonal natural variability of the data, all records point out an unequivocal anthropogenic contribution to mid-troposphere pollution during the second half of the 20th century. These changes could have been associated also to modifications of the mean long-range atmospheric circulation patterns within the Mediterranean basin.